A Guiding Principle for Strengthening Crosslinked Polymers: Synthesis and Application of Mobility‐Controlling Rotaxane Crosslinkers. (25th January 2019) - Sawada, Jun; Aoki, Daisuke; Otsuka, Hideyuki; Takata, Toshikazu
Abstract: Three component mobility controlling vinylic rotaxane crosslinkers with two radically polymerizable vinyl groups (RC_R s) were synthesized to prove that the mobility of the components of the RC_R s plays a crucial role in determining the properties of rotaxane‐crosslinked polymers (RCPs). RC_R s (R=H, Me, or Et) were obtained from living ring‐opening polymerization. RCP_Et was prepared using RC_Et, which exhibits the lowest component mobility. The low component mobility is reflected in inferior mechanical strength and stretching ability in tensile stress tests compared to components with good (R=Me) and high (R=H) mobility. However, RCP_Et exhibited significantly higher stress and strain values than the corresponding covalently crosslinked polymers (CCP_R s). These results indicate that a suitable component mobility substantially enhances the mechanical strength of RCPs. This behavior could serve as a guiding principle for the molecular design of advanced RCs. Abstract : Rotaxan‐Vernetzer (RC_R) mit zwei radikalisch polymerisierbaren Vinylgruppen wurden synthetisiert, um damit die Beweglichkeit der Komponenten in rotaxanvernetzten Polymeren (RCP_R) zu bestimmen. RCP_Et zeigt die geringste Komponentenbeweglichkeit, was sich in einer geringeren mechanischen Festigkeit und Dehnfähigkeit im Vergleich zu RCPs mit guter (R=Me) und hoher (R=H) Beweglichkeit äußert.